Southern Scoundrels : Grifters and Graft in the Nineteenth Century - Baker, Bruce E., 1971-; Forret, Jeff, 1972- (Book collections on Project MUSE., 2021)
"The history of capitalist development in the United States is long, uneven, and overwhelmingly focused on the northern states. Recent years have witnessed an explosion of works on capitalism in the South. Still, these have primarily been macroeconomic studies emphasizing the role of the cotton economy in global trading networks. Less understood is how capitalism took root and functioned in all its variated facets in the nineteenth-century South. This volume explores the lesser-known aspects of those processes: the shady and unscrupulous peddlers, preachers, slave traders, war profiteers, thieves, and marginal men who seized the available opportunities to get ahead and made the southern economy what it was. The ten chapters of 'Southern Scoundrels: Grifters and Graft in the Nineteenth-Century South' eschew dry economic theory in favor of narrative storytelling as engaging and seductive as the set of shifty and corrupt characters under examination. The essays cover the chronological sweep of nineteenth-century southern history, from the antebellum era, through the tumultuous and chaotic Civil War years, and into Reconstruction and beyond. The geographic coverage is equally broad, with chapters encompassing the Chesapeake, South Carolina, the Lower Mississippi Valley, Texas, Missouri, and Appalachia. 'Southern Scoundrels' offers a series of social histories indicative of the nineteenth-century southern economy and the changes wrought by the capitalist transformation. Tracing that story through the kinds of smarmy individuals who made it happen makes it accessible to a wide range of readers interested in the region's history"--